The Synthesis and Evaluation of Novel Core-Shell Nanostructured Metal Oxides for Cancer Targeting - Patel, Kunal Kamleshkumar (Curtin University, 2016)
This thesis details the synthesis and characterisation of novel silica coated Fe3O4-ZnO core-shell nanostructures for applications in target-specific photodynamic cancer therapy. While the silica shell was outfitted with folic acid for promoting cell specificity, dansyl chloride for fluorescent imaging and polyethylene glycol for biocompatibility and stability, the photoactive core showed significant in-vitro photo-killing ability. The methods and results established in this thesis provide researchers of cancer therapeutics new insights into nanoparticle design and modification schemes.